In vitro effects of different biomaterials on canine dental pulp stem cells - Marx, Robert; Nemec, Ana; Kocjan, Andraž; Voga, Metka (Frontiers in Veterinary Science, 2026)
ObjectiveRegenerative endodontic treatments are being developed in veterinary dentistry. The aim of this study was to evaluate the biocompatibility and odontogenic potential of three biomaterials, ProRoot® MTA (MTA), RS + ™ (RS+), and CellFoam™ (CF), on canine dental pulp stem cells (cDPSCs) under conditions simulating early and clinically relevant exposures.MethodscDPSCs were isolated from three healthy dog teeth extracted for clinical reasons and characterized by flow cytometry (CD44+/CD90+/CD29+/CD34−) and multilineage differentiation. Cells were cultured with material suspensions (acute cytotoxic effect) or conditioned medium (physiologically relevant effect). Metabolic activity and cell viability were assessed by MTT and live/dead assays. Osteogenic/odontogenic differentiation was evaluated by Alizarin Red S staining and RT–qPCR for RUNX2, ALPL, and MMP13 expression.ResultsIn suspension cultures, compared with MTA and RS+, CF maintained significantly higher metabolic activity and cell viability across several dilutions, indicating lower acute cytotoxicity. Under conditioned exposure, no significant differences among materials were observed, reflecting the dilution and buffering effects that mitigate early reactivity. All the materials supported Alizarin Red S-positive mineral deposition, with a significant difference at D3, when ARS staining of cDPSCs was greater in cells conditioned with MTA than in those conditioned with CF. Gene expression analysis revealed lower RUNX2 and ALPL expression in MTA-conditioned cells, suggesting, together with ARS staining, progression toward a more advanced osteogenic or odontogenic differentiation stage. MMP13 expression remained comparable across materials.ConclusionMTA, RS+, and CF demonstrated overall biocompatibility with cDPSCs and supported odontogenic differentiation under clinically relevant conditions. CF exhibited the lowest acute cytotoxicity, indicating its potential as a carrier for DPSC-based regenerative endodontic applications. These findings support the translational importance of in vitro cDPSC models for evaluating biomaterial performance in veterinary regenerative endodontics.